Same-sex marriage, the great equalizer - Alexey Parakhonyak; Sergey V. Popov (Cardiff University, Cardiff Business School, 2019)
When limited to heterosexual marriage, agents of different genders are not guaranteed to harvest the same payoff even conditional on having the same type, even if all other factors, such as search costs or the distribution of partner types, are same across genders. If same-sex marriage is legalized and there is a positive mass of agents who find marriage with both sexes acceptable, then only symmetric equilibria survive in symmetric environments.
Keywords: C78; D1; 330; marriage markets; matching; gender equality; same-sex marriage